Dealing with police stops: how young people with ethnic minority backgrounds narrate their ways of managing over-policing in the Nordic countries - Saarikkomäki, Elsa (Policing and society, 2023)
Research shows that young people within ethnic minorities are subjected to police control more often than others, which seems to have a damaging effect on their trust in the police as well as on their wider sense of belonging. What is less often researched is how these young people deal with being over-policed. This article explores narratives of over-policing from those targeted by the police in Denmark, Finland, Norway and Sweden. By highlighting the patterns in these narratives in cross-national interview data, we seek to understand how young people manage interactions with the police and being stigmatised and ethnically profiled. The article distinguishes between three categories of narratives, (a) practical (b) emotional and (c) analytical, which the young people invoke and employ when they discuss their experiences and assessments of the police. The article concludes that we need a more dynamic perspective to understand and analyse how targeted groups constitute agency, resistance and active responses to ethnic profiling or labelling. Being young and belonging to an ethnic minority in the Nordic countries means developing and employing everyday tactics to both manage and account for the risk of police encounters.